Current status and development suggestions of CCUS technology in China under the "Double Carbon" strategy - Qihui HU; Yuxing LI; Jian ZHANG; Xinran YU; Hui WANG; Wuchang WANG; Buze YIN; Jiyu GONG (You-qi chuyun, 2022)
Carbon Capture, Utilization and Storage (CCUS) is an effective way to reduce industrial CO2 emission on large scale at present. The development status of key links of CCUS at home and abroad was analyzed systematically. Currently, the post-combustion CO2 capture technology is relatively mature, the separation system of pre-combustion capture technology is complex, and the oxygen-enriched combustion technology with a high power consumption for producing oxygen, but it is required to reduce the cost of CO2 capture and energy consumption for industrial applications. Although the technical strength has been achieved in China in terms of technology, safety and standard for CO2 pipeline transportation, no project verification has been performed and no technical standards of CO2 pipeline are available. In addition, the domestic CO2 storage projects are relatively small in scale, and the requirements for industrial promotion in terms of reinjection scheme, ground process system and CO2 leakage monitoring are not satisfied. Rich experience has been cumulated from the low CO2 utilization in the development of oil and gas fields, chemical production and other areas. So, CO2 storage cost should be reduced by improving the storage and utilization in the future. The research results can provide reference to the project demonstration and commercialized development of CCUS.